The private and the public (2007)
In 1983, at a seminar organized to prepare the third volume of the History of private life that he directed with Georges Duby, Philippe Ariès proposed a double definition of the dichotomy between the public and the private (Ariès, 1989, pp. 7-19 ). The fi